Mathematics anxiety: Identifying and reducing its impact in the elementary classroom - Bruce, Maureen (2017)
Mathematics anxiety has been identified as a significant impediment to mathematics achievement, which furthermore negatively affects at least 30% of the population of many Western countries. The potential impact on both personal and overall economic growth and development is huge, and consequently it needs to be addressed both in terms of assessment and intervention. Given that the effects materialise more clearly in middle and high school, it often goes unnoticed at the elementary level, where the seeds are inevitably sown. In contrast to the majority of studies which focus on college students and pre-service teachers, this study looks at the role that more experienced elementary teachers can play in contributing to the cycle of mathematics avoidance and poor performance by examining their attitudes, values and beliefs, in addition to identifying any anxiety towards mathematics which can be passed on to students. Participants shared their views by engaging in semi-structured interviews, and the data were analysed to establish common themes. Findings show that the phenomenon is very much in evidence among experienced elementary teachers, less than that recorded for pre-service teachers but on a par with figures for the general population at 28.5%. Furthermore, it is particularly evident in female teachers. One of the most common reasons given is teachers’ own past experiences with educators and the way mathematics was taught. The findings also show mixed attitudes towards the subject and a range of views on the innate ability of students to do well in it. Despite this, there is general consensus that all students can improve and that ability is neither fixed nor dependent upon gender. Finally, suggestions on how to identify and address anxiety in both teachers and students are examined in an attempt to break the cycle of poor performance, avoidance and negative experiences surrounding mathematics in the elementary classroom.